Використання короткострокових тестів для дослідження мутагенної активності пестицидних препаратів - Сенченко, Т.В.; Болтіна, І.В.; Костик, О.Л.; Ткачук, О.М.; Лепьошкін, І.В.; Кравчук, О.П. (Актуальні проблеми транспортної медицини, 2010)
Показано, что исследование токсичных свойств пестицидных препаратов генериков, должны быть неотъемлемой частью исследований мутагенной активности этих веществ, которые следует проводить только в комплексе с применением не менее трех тестов. It is shown that research of toxic properties of pesticidal preparations generikov should be an integral part of researches of mutagen activity of these substances. The complex of not less than three tests should be contained at these researches.